Application of Spiritual Therapy to Reduce Stress Levels, Emotions and Understanding of the Religion of Islam in Patients of Drug Abuse - Muhammad Al-Amin R. Sapeni; Toar Calvin Christo Paat; Helmi Juwita; Yeni Iswari (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Goals in study This For know influence gift spiritual healing for lower level stress , emotion , and understanding about the Islamic religion to patient blame NAPZA use Research design This that is literature review , search article using Pudmed , Google Schoolar , and Proquest databases . As for the criteria induction that is focus to decline level stress , emotion and understanding of the Islamic religion use spiritual healing , database published at least 10 years finally , there were 15 articles found and only 10 articles that were suitable with study This There are 10 articles included in the journal study this . From the results study obtained that gift Islamic spiritual healing can influence decline level stress , emotion and understanding about the patient's religion blame use NAPZA. a gift Islamic spiritual healing can influence decline level stress , emotion and understanding about the patient's religion blame use NAPZA